STUDI TEKNIK PERMAINAN HARMONIUM PADA KESENIAN KATUMBAK DI KORONG MUARO NAGARI KURAI TAJI KECAMATAN NAN SABARIS (ANALISIS PROSES TRAINING ERI SUSANTI) - Salsabila, Ajari; Wimbrayardi (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study uses a qualitative approach with a descriptive method. The research object is the Harmonium playing technique in the art of Katumbak, focusing on the training process that shapes the players' skills. The research data consists of primary and secondary data. The main research instrument is the researcher, supported by writing tools and documentation equipment. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis is conducted through data reduction, data presentation, and drawing conclusions and verification. Research results show that Eri Susanti's harmonium playing technique in Katumbak art is marked by mastery of stable bellow control, resulting in an uninterrupted flow of sound, the use of flexible and efficient fingering techniques, and the application of simple chords to support harmony, which are then developed through characteristic melodies and ornamentation that follow the vocal patterns and rhythms of Gandang, making the performance sound lively and cohesive. Eri Susanti's training process took place gradually from the age of 8 until she became proficient at the age of 68 through non-formal learning by observing, imitating, and repeating without using musical notation, starting from sound recognition, mastering melodies, to the ability to improvise in performances. This was reinforced through direct involvement in practice and performances, thus developing musical sensitivity, technical skills, and the ability to adapt to other instruments. Consequently, Eri Susanti not only served as a Harmonium player, but also as the musical control centre determining the direction and quality of Katumbak performances and became an important figure in the process of cultural heritage transmission in the community.